Pengaruh Kinerja Bank Terhadap Kepercayaan Nasabah Bank Syariah Indonesia (BSI) Pasca Merger - Nurul Laily Abdulloh Putri; Wahyu Dwi Warsitasari (WADIAH, 2022)
The merger of three state-owned Islamic banks namely BRI Syariah Bank, BNI Syariah and Mandiri Syariah into one entity under the name Bank Syariah Indonesia (BSI) in early February 2021 resulted in various changes both from the internal and external sides of the company. One of the parties who feel the impact of this merger is the customer from the three Sharia Banks, this study aims to determine the effect of the bank's performance which in this case is seen from the quality of service and customer satisfaction on the level of customer trust after the merger. This research uses quantitative methods and data collection is done through the distribution of questionnaires for primary data. The sampling technique used is purposive sampling, with respondents in this study totaling 100 customers with predetermined characteristics. Then the data obtained were analyzed using multiple linear regression analysis, the results showed that service quality and customer satisfaction had a significant effect on the level of customer confidence in Bank Syariah Indonesia (BSI) after the merger. Keywords: Bank Syariah Indonesia, Merger, Service Quality, Customer Satisfaction, Customer Trust